KEPEMIMPINAN KEPALA SEKOLAH DASAR DI DAERAH TERPENCIL (STUDI MULTI KASUS DI SDN 2 BAKALAN DAN SDN 2 KEPYAR PURWANTORO KABUPATEN WONOGIRI) - Muhani Muhani; Ali Imron; Kusmintardjo Kusmintardjo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
The study aims to describe the leadership of school principals in a remote area in SDN 2 Bakalan and SDN 2 Kepyar Purwantoro, Wonogiri. This study used descriptive qualitative approach with multiple case study design. Data collection techniques with interviews, non-participant observation, and study documentation. The data analysis consisted of analysis of individual cases and cross-case analysis. Checking the validity of the data using the test credibility, transferability, dependability, and testing confirmability The results are the first to use the leadership style is the style of participation and delegation. Second, application of force participation in the main tasks of teachers, being force delegation on additional duties of teachers. Third, support the leadership of school principals in remote areas obtained from external and internal. External support namely: special allowances for teachers, school support committee, and teacher competence and harmonious atmosphere. Internal support are: experience of organizing, provision of education, self-reliance and innovativeness principal. Fourth, barriers to leadership comes from the geographical conditions of schools, provision of science and the demands of society. Fifth, efforts to overcome the barriers that the special allowance equalization policy, strengthen personal relationships, and intensive communication with the committee and parentsPenelitian ini bertujuan mendeskripsikan kepemimpinan kepala sekolah dasar di daerah terpencil di SDN 2 Bakalan dan SDN 2 Kepyar Purwantoro Wonogiri. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan rancangan studi multi kasus. Teknik pengambilan data dengan wawancara, observasi non participant, dan study dokumentasi. Analisis data terdiri dari analisis kasus individu dan analisis lintas kasus. Pengecekan keabsahan data menggunakan uji credibility, transferability, dependability, dan pengujian confirmability Hasil penelitian, yaitu pertama gaya kepemimpinan yang digunakan adalah gaya partisipasi dan delegasi. Kedua, penerapan gaya partisipasi dalam tugas pokok guru, sedang gaya delegasi pada tugas tambahan guru. Ketiga, dukungan kepemimpinan kepala sekolah dasar di daerah terpencil didapatkan dari eksternal dan internal. Dukungan eksternal yaitu: tunjangan khusus untuk guru, bantuan komite sekolah, dan kompetensi serta suasana harmonis guru. Dukungan internal yaitu: pengalaman berorganisasi, bekal pendidikan, kemandirian dan daya inovasi kepala sekolah. Keempat, hambatan kepemimpinan berasal dari kondisi geografis sekolah, bekal keilmuan, dan tuntutan masyarakat. Kelima, upaya menyelesaikan hambatan yaitu dengan kebijakan pemerataan tunjangan khusus, memperkuat hubungan personal, dan komunikasi intensif dengan komite dan wali murid